Lacticaseibacillus rhamnosus HN001 alters the microbiota composition in the cecum but not the feces in a piglet model - Young, Wayne; Maclean, Paul; Dunstan, Kelly; Ryan, Leigh; Peters, Jason; Armstrong, Kelly; Anderson, Rachel; Dewhurst, Hilary; van Gendt, Melanie; Dilger, Ryan N.; Dekker, James; Haggarty, Neill; et al. (Frontiers in Nutrition, 2022)
The probiotic Lacticaseibacillus rhamnosus strain HN001 has been shown to have several beneficial health effects for both paediatric and maternal groups, including reduced risk of eczema in infants and gestational diabetes and postnatal depression in mothers. While L. rhamnosus HN001 appears to modify immune and gut barrier biomarkers, its mode of action remains to be fully elucidated. To gain insights into the role of HN001 on the infant microbiome, the impacts of L. rhamnosus HN001 supplementation was studied in 10-day old male piglets that were fed either infant formula, or infant formula with L. rhamnosus HN001 at a low (1.3 x 105 CFU/ml) or high dose (7.9 x 106 CFU/ml) daily for 24 days. The caecal and faecal microbial communities were assessed by shotgun metagenome sequencing and host gene expression in the caecum and colon tissue was assessed by RNA-seq. Piglet faecal samples showed only modest differences between controls and those receiving dietary L. rhamnosus HN001. However, striking differences between the three groups were observed for caecal samples. While total lactobacilli were significantly increased only in the high dose L. rhamnosus HN001 group, both high and low dose groups showed an up to two-fold reduction across the Firmicutes phylum and up to four-fold increase in Prevotella compared to controls. Methanobrevibacter was also decreased in HN001 fed piglets. Microbial genes involved in carbohydrate and vitamin metabolism were among those that differed in relative abundance between those with and without L. rhamnosus HN001. Changes in the caecal microbiome were accompanied by increased expression of tight junction pathway genes and decreased autophagy pathway genes in the caecal tissue of piglets fed the higher dose of L. rhamnosus HN001. Our findings showed supplementation with L. rhamnosus HN001 caused substantial changes in the caecal microbiome with likely consequences for key microbial metabolic pathways. Host gene expression changes in the caecum support previous research showing L. rhamnosus HN001 beneficially impacts intestinal barrier function. We show that faecal samples may not adequately reflect microbiome composition higher in the gastrointestinal tract, with the implication that effects of probiotic consumption may be missed by examining only the faecal microbiome.